One Kind Special Gauss Sums and their Mean Square Values. (9th July 2021) - Zhao, Jianhong; Gao, Jiejie
Abstract : In this paper, we introduce one kind special Gauss sums; then, using the elementary and analytic methods to study the mean value properties of these kind sums, we obtain several exact calculating formulae for them.